2002
DOI: 10.1063/1.1436467
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio adiabatic and diabatic energies and dipole moments of the KH molecule

Abstract: An ab initio adiabatic and diabatic study of the KH molecule is performed for all states below the ionic limit [i.e., K (4s, 4p, 5s, 3d, 5p, 4d, 6s, and 4f)+H(1s)] in 1Σ+ and 3Σ+ symmetries. Adiabatic results are also reported for 1Π, 3Π, 1Δ, and 3Δ symmetries. The ab initio calculations rely on pseudopotential, operatorial core valence correlation, and full valence CI approaches, combined to an efficient diabatization procedure. For the low-lying states, our vibrational level spacings and spectroscopic consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 34 publications
2
32
2
Order By: Relevance
“…[9] . Moreover, the values are considerably better than the theoretical values of 293.1 and 801 cm −1 given by Ross et al [28] and Khelifi et al [8] , respectively. Using schemes 2 and 3, the R e s obtained are close to those of Ross et [9] .…”
contrasting
confidence: 39%
See 1 more Smart Citation
“…[9] . Moreover, the values are considerably better than the theoretical values of 293.1 and 801 cm −1 given by Ross et al [28] and Khelifi et al [8] , respectively. Using schemes 2 and 3, the R e s obtained are close to those of Ross et [9] .…”
contrasting
confidence: 39%
“…Lee et al calculated the 1 Σ + and 3 Σ + states of KH which were dissociated into the 4s-6p states of K at the level of the configuration interactions and found that most of states show the undulating potential curves [7] . Khelifi et al performed ab initio adiabatic and diabatic studies of the KH molecular for all the states below the ionic limit [i.e., K(4s, 4p, 5s, 3d, 5p, 4d, 6s, and 4f)+H(1s)] in 1 Σ + and 3 Σ + symmetries at the level of full valence CI approaches [8] . They presented the spectroscopic constants for the states and obtained seven vibrational levels of B 1 Π.…”
mentioning
confidence: 99%
“…In this study, CsLi + having only one active electron will be one of the simplest heteromolecular systems, thus reducing the computing time. The present work follows our studies on many diatomic systems, such as KH, RbH, CsH, NaH, and (LiNa and LiNa + ) [20][21][22][23][24], where we used the same techniques. For all of the molecules, a remarkable accuracy was obtained, showing the validity of the approach.…”
mentioning
confidence: 99%
“…The realization of the complete configuration interaction is thus easily allowed. This study has been performed using the Toulouse package code …”
Section: Methodsmentioning
confidence: 99%
“…In our research group we have applied the diabatization method on several diatomic systems like CaH + , LiH, CsH, KH, RbH, KLi, and RbLi in order to get insight and also to study the nonadiabatic effects such as the adiabatic correction and the radial coupling. Accurate data for the potential energy curves, the spectroscopic constant, permanent and transition dipole moments have been produced by our group for SrH + .…”
Section: Introductionmentioning
confidence: 99%